From deadly to life-saving effects: antimicrobial and antibiofilm effects of tarantula cubensis extract on bacterial and fungal pathogens - Elif AYDIN (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Every year, many people around the world lose their lives due to antibiotic resistance therapy. These resistances pose serious health threats to both individuals and societies, making even simple services difficult to treat. Antibiotic resistance not only affects medical practices, but also causes a huge economic burden on health systems. In this study, Tarantula cubensis spider venom was investigated to produce new antimicrobial agents effective against Gram (+) and Gram (-) bacteria and Candida species. Antimicrobial and antibiofilm activity of T. cubensis extract against microorganisms were tested using minimum inhibition, resazurin and time killing curve methods. MIC values of T. cubensis extract were determined as 14.3-0.45 mg/mL by broth dilution method and 14.3-3.58 mg/mL by resazurin method for the investigated pathogens. Time-kill curve studies confirmed the growth retardant, bacteriostatic/ fungistatic and bactericidal/ fungicidal activity of T. cubensis extract. Antibiofilm studies also showed that T. cubensis extract significantly inhibited and blocked biofilm formed by pathogens (melittin 8-82%, apamin 1.8-78%). T. cubensis was effective in inhibiting biofilm formation (from 99.98% to 75.68%) and eradicating biofilm (from 32.97% to 4.67%) at the highest concentration. T. cubensis extract was found to have high antibacterial and antibiofilm properties. Such natural poisons offer a promising and powerful solution to control microbial populations, combat pathogens, and protect human and animal health.